FORMULASI UMUM METODE ITERASI DENGAN ORDE KONVERGENSI ENAM - Dewi Khairati Putri; M. Imran; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the General Formulation of Iterative Method, which requires three function evaluations and one derivative function evaluation. Analytically it is showed, using the Taylor expansion and geometric series, that the General Formulation of Iterative Method has a convergence of order six. Furthermore, by choosing the values of certain parameters in the General Formulation of Iterative Method, several well-known iterative methods, which have three function evaluations and one derivative function evaluation, are obtained. Comparison between the proposed method and well-known methods are done by looking at the number of iterations and number of function evaluation. In addition, comparisons are also made through Basins of Attraction of the methods discussed.